TINJAUAN KRIMINOLOGI KRITIS TERHADAP KEBIJAKAN NEGARA DALAM MELINDUNGI PEREMPUAN BURUH MIGRAN PEKERJA RUMAH TANGGA - Rizky Nur Haryani (Jurnal Kriminologi Indonesia, 2011)
Violence against women migrant domestic workers is not a new discourse in Indonesia. The types of violence which have always been for public consumption are matters relating physical violence, psychological, sexual, and economic. Therefore, the study seeks to uncover the abuses faced by them from another viewpoint, namely critical criminology, to see that the violence experienced by them is more due to the imbalance of power between the government with them, there is also framework of criminology and public policy, economic political crimes, and state crime. Varieties of research studies and field-explanatory types of research had been selected researcher to analyze the existing problems by using the above framework by. The result showed that the Government participated in the structural violence implicatd to them through policy making.